A Juridical Analysis of Formalistic Legality and Substantive Justice in Protecting Children Born Out of Wedlock - Nayla Putri Abdullah; Irsyaf Marsal (Lambung Mangkurat Law Journal, 2025)
This study provides a comprehensive and in-depth examination of how the law protects children born out of lawful marriage. Its primary focus is on the provisions contained in Law Number 1 of 1974 concerning Marriage and the reinforcement provided by Constitutional Court Decision Number 46/PUU-VIII/2010. The main issue highlighted in this research is the persistent uncertainty regarding the legal status and civil rights of children born out of lawful marriage, particularly when their parents’ marriage has not been officially registered. To address this issue, the study employs a normative legal research method, using a written regulation approach combined with case studies. This enables an analysis of how the law is applied in practice concerning the status of children born out of wedlock, through examination of court decisions and relevant legal provisions. The findings indicate that Constitutional Court Decision Number 46/PUU-VIII/2010 brought significant changes to the Indonesian family law system. The decision expands recognition of the legal relationship between children born out of wedlock and their biological fathers, provided that strong evidence is available, such as DNA test results. Consequently, the ruling emphasises the importance of respecting the fundamental rights of every child, regardless of their birth status, and encourages the state to guarantee children’s rights to identity and legal status through mechanisms such as itsbat nikah (marriage validation) and the determination of parentage in court. Overall, this study confirms that legal protection for children born out of wedlock represents a concrete application of the principles of substantive justice, legal certainty, and non-discriminatory treatment as mandated by the constitution and the national legal system of Indonesia.